Edukasi Pola Hidup Bersih dan Sehat Pada Siswa SMPN 8 Kubu Raya - Nurdiansyah, Syarif Irwan (Indonesian Journal Publisher, 2024)
The high morbidity rate in school-age children is caused by various factors, especially irregular eating habits, unhealthy eating and snacks in random places. Consuming healthy, balanced nutritious food is one part of a clean and healthy lifestyle, which aims to improve health and avoid various diseases. Community service activities (PKM) with the topic of PHBS education for students at SMPN 8 Kubu Raya aim to introduce and increase school age children's knowledge about PHBS through education on healthy, balanced nutritious eating patterns to improve health. The activity was attended by 30 students, who were expected to be able to apply the material presented and at the same time become agents of change in their families or the environment where they live. This activity is carried out using an educational lecture method, related to various diseases that often appear among school-age children and are caused by irregular eating habits or patterns as well as snacks in random places where the cleanliness of the place or the cooking process is not guaranteed. In this activity, we also watched YouTube videos together regarding why teenagers should adopt a healthy lifestyle and what can be done to implement this. The PKM activity went smoothly and participants participated enthusiastically during the activity. Evaluation of activities shows that students at SMPN 8 Kubu Raya understand the importance of maintaining a healthy, balanced, nutritious diet in achieving excellent health for school children.